Do CEOs Matter? - Morten Bennedsen; Francisco Pérez-González; Daniel Wolfenzon (Copenhagen Business School (CBS), Department of Economics, 2007)
Estimating the value of top managerial talent is a central topic of research that has attracted widespread attention from academics and practitioners. Yet, testing for the importance of chief executive officers (CEOs) on firm outcomes is challenging. In this paper we test for the impact of CEOs on performance by assessing the effect of (1) CEO deaths and (2) the death of CEOs immediate family members (spouse, parents, children, etc), which arguably affects CEOs focus. Using a unique dataset from Denmark, we find that CEO (but not board members ) own and family deaths are strongly correlated with declines in firm operating profitability, investment and sales growth. Our CEO shock-outcome analysis allows us to identify the shocks that are the most (least) meaningful for CEOs: the death of children and spouses (mothers-in-law). We show that individual CEO, firm and industry characteristics seem to affect the impact of these shocks. In particular, CEO effects are larger (lower) for longer-tenured (older) CEOs and for those managers with large investment fixed effects. CEO shocks are relevant across the size distribution of firms but are concentrated on those firms that invested heavily in the past. Lastly, we find that CEO shocks tend to be larger in rapid growth, high investment and R&D intensive industries. Overall, our findings demonstrate managers are a key determinant of firm performance.
hdl:10398/7523
Keywords: G10; 330